Functional potential of intermediate wheatgrass (IWG) in bread formulations: role of base flour gluten strength - Md Ahmadul Islam; Jayani Kulathunga; Yun Zhao; Shahidul Islam (Applied Food Research)
Intermediate wheatgrass (IWG, Thinopyrum intermedium), a perennial grain rich in dietary fiber, protein, and antioxidants, considered as a functional ingredient for nutritionally enhanced baked goods. However, its limited use in breadmaking is due to weak gluten formation associated with high fiber content. While base flour gluten strength is crucial in determining the allowable level of IWG flour without compromising bread quality, systematic comparisons across flours with varying gluten strengths are limited. This study evaluates IWG flour as a partial substitute in three wheat flours: all-purpose (AP, medium gluten), whole wheat flour (WWF, medium-low gluten), and hard red spring (HRS, high gluten), to determine optimal inclusion levels that preserve quality and enhance nutrition. Blends with 10 %, 20 %, and 30 % IWG flour were assessed for proximate composition, protein and starch functionality, dietary fiber, total phenolic content, antioxidant activity, dough rheology, and bread quality. Despite its higher protein content (22.65 %), IWG showed the lowest unextractable polymeric protein, aggregation energy, and HMW glutenins. Base flours varied in their ability to incorporate IWG: HRS supported up to 20 % and AP up to 10 % without adversely affecting dough or bread quality. These levels significantly improved bread nutrition: fiber increased from 3.20 to 4.35 % and 2.95 to 3.65 %; phenolics from 18.73 to 19.96 % and 12.34 to 16.11 %; and antioxidant activity from 4.37 to 8.07 and 2.51 to 4.67 mg Trolox/100 g, respectively. WWF was not suitable for IWG inclusion. Findings highlight the importance of base flour gluten strength in leveraging IWG's health benefits without compromising bread quality.